2018
DOI: 10.3389/fpsyt.2018.00352
|View full text |Cite
|
Sign up to set email alerts
|

Course of Mental Health in Refugees—A One Year Panel Survey

Abstract: Background: Cross-sectional studies indicate that a substantial proportion of refugees have psychiatric disorders. However, longitudinal studies on the course of psychiatric symptoms and on influencing factors are scarce. The current study investigates the development of symptoms in an untreated refugee sample in Germany and seeks to identify potential predictors.Methods: Over the course of 1 year, 57 refugees participated in monthly assisted self-reports on the phone assessing emotional distress. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 68 publications
(73 reference statements)
3
50
3
3
Order By: Relevance
“…Giacco, Laxhmant, and Priebe (2018), as well as several other studies, emphasize the detrimental and aggravating effects that adverse conditions in a host country can have on refugees' mental health. Similar conclusions are reached by Bakker, Dagevos, and Engbersen (2014) and Kaltenbach et al (2018), while Porter and Haslam (2005) identify living in institutional accommodation and experiencing restricted economic opportunity as risk factors for mental health outcomes. Studies investigating mental health outcomes in relation to post-migration experiences overwhelmingly conclude that the consequences of exposure to violence and trauma can be mitigated by early psychological support, reduced duration in asylum facilities, and support for early absorption into the labor market.…”
Section: Discussion and Policy Implicationssupporting
confidence: 62%
“…Giacco, Laxhmant, and Priebe (2018), as well as several other studies, emphasize the detrimental and aggravating effects that adverse conditions in a host country can have on refugees' mental health. Similar conclusions are reached by Bakker, Dagevos, and Engbersen (2014) and Kaltenbach et al (2018), while Porter and Haslam (2005) identify living in institutional accommodation and experiencing restricted economic opportunity as risk factors for mental health outcomes. Studies investigating mental health outcomes in relation to post-migration experiences overwhelmingly conclude that the consequences of exposure to violence and trauma can be mitigated by early psychological support, reduced duration in asylum facilities, and support for early absorption into the labor market.…”
Section: Discussion and Policy Implicationssupporting
confidence: 62%
“…Several studies have confirmed the persistence of mental problems even after more than three or five years in the host country [30,54]. On the one hand, a path analysis performed to investigate post-migration psychological symptoms among refugees in Germany found on average similar PTSD and depressive symptoms over the course of one year [27]. On the other hand, a previous study by our group on Arabic-speaking asylum seekers suggested participants with mental distress have shorter periods of stay in Germany compared to the asylum seekers without mental distress.…”
Section: Discussionmentioning
confidence: 93%
“…Regarding previous studies investigating risk factors of mental disorders in Syrian refugees, a predominant focus on the impact of experienced traumatic events stands out. Research evidence suggests that there is a strong positive correlation between the number of traumatic events and emotional disorders, especially post-traumatic stress symptoms [4,20,26,27]. Alpak et al [6] for instance found that Syrian refugees who experienced two or more traumatic events were at higher risk of developing PTSD than others.…”
Section: Introductionmentioning
confidence: 99%
“…There are a wide range of events and contexts that qualify as potentially traumatizing, and within each of these the “dose” of exposure (i.e., magnitude, frequency) has established associations to functional impairment (see, for instance, Neuner et al, 2004; Elbert et al, 2006; Kaltenbach, Schauer, Hermenau, Elbert, & Schalinski, 2018). As such, we selected studies that cover a wide range of trauma exposure types and trauma‐affected populations, from adolescents growing up in conflict zones ( Shaheen et al, ) or experiencing flight and displacement ( Sill, Popov, Schauer, & Elbert, 2019) to adolescent victims of childhood abuse ( Iffland et al, 2019), adult combat‐exposed veterans ( Grupe, Imhoff‐Smoth, Wielgosz, Nitschke, & Davidson, 2019; Macatee et al, 2019), African civil war survivors ( Conrad et al, 2018; Jovanovic et al, ), adults treated for fear and anxiety disorders including PTSD from various types of trauma ( Harricharan et al, 2019; Jovanovic et al, ; Sambuco, Bradley, Herring, Hillbrandt, & Lang, 2019) and childhood abuse ( Lis et al, 2019).…”
mentioning
confidence: 99%
“…There are a wide range of events and contexts that qualify as potentially traumatizing, and within each of these the "dose" of exposure (i.e., magnitude, frequency) has established associations to functional impairment (see, for instance, Neuner et al, 2004;Elbert et al, 2006;Kaltenbach, Schauer, Hermenau, Elbert, & Schalinski, 2018). As such, we selected studies that cover a wide range of trauma exposure types and trauma-affected populations, from adolescents growing up in conflict zones (Shaheen et al, 2018) or experiencing flight and displacement (Sill, Popov, Schauer, & Elbert, 2019) to adolescent victims of childhood abuse (Iffland et al, 2019), adult combat-exposed veterans (Grupe, Imhoff (Lis et al, 2019).…”
mentioning
confidence: 99%